PTX-induced hyperexcitability affects dendritic shape and GABAergic synapse density but not synapse distribution during Manduca postembryonic motoneuron development - Meseke, Maurice; Evers, Jan-Felix; Duch, Carsten (Journal of comparative physiology. A, Neuroethology, sensory, neural, and behavioral physiology, 2009)
During the metamorphosis of the holometabolous insect, Manduca sexta, the postembryonic acquisition of adult specific motor behaviors is accompanied by changes in dendritic architecture, membrane currents, and input synapses of identified motoneurons. This study aims to test whether increased activity affects dendritic architecture and sub-dendritic input synapse distribution of the identified flight motoneuron 5 (MN5). Systemic injections of the chloride channel blocker, picrotoxin (PTX), during early pupal stages increase pupal reflex responsiveness, but overall development is not impaired. MN5 input resistance, resting membrane potential, and spiking threshold are not affected. Bath application of PTX to isolated ventral nerve cords evokes spiking in pupal and adult flight motoneurons. Quantitative three-dimensional reconstructions of the dendritic tree of the adult MN5 show that systemic PTX injections into early pupae cause dendritic overgrowth and reduce the density of GABAergic inputs. In contrast, the distribution patterns of GABAergic terminals throughout the dendritic tree remain unaltered. This indicates that increased overall excitability might cause dendritic overgrowth and decreased inhibitory input during postembryonic motoneuron remodeling, whereas sub-dendritic synapse targeting might be controlled by activity-independent signals. Behavioral testing reveals that these neuronal changes do not impede the animal’s ability to fly, but impair maximum flight performance.